Schefflera serpentinicola - Tsen, S.; Colin Ruzelion Maycock; Khoo, E.; Nilus, R.; Sugau, J.; Tanggaraju, S.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2020)
Schefflera serpentinicola is only known from Wuluh river, Kinabalu Park. The estimated area of occupancy (AOO) and extent of occurrence (EOO) are both 4 km2. The most plausible threat that could affect this species is climate change, in the form of temperature extremes and droughts. If this was to occur it could rapidly drive the species towards Critically Endangered or Extinct within a short space of time. Hence it is assessed as Vulnerable. Schefflera serpentinicola is endemic to Sabah, Malaysia. It is only known from Wuluh river, Kinabalu Park.